1993
DOI: 10.2514/3.11594
|View full text |Cite
|
Sign up to set email alerts
|

Effect of tabs on the flow and noise field of an axisymmetric jet

Abstract: The effect of vortex generators, in the form of small tabs projecting normally into the flow at the nozzle exit, on the characteristics of an axisymmetric jet is investigated experimentally over the jet Mach number range of 0.3-1.81. The tabs eliminate screech noise from supersonic jets and alter the shock structure drastically. They distort the jet cross section and increase the jet spread rate significantly. The distortion produced is essentially the same at subsonic and underexpanded supersonic conditions. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
135
3
1

Year Published

1997
1997
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 319 publications
(153 citation statements)
references
References 28 publications
10
135
3
1
Order By: Relevance
“…Possible physical mechanisms by which tabs produce streamwise vortices has been discussed by Samimy, Zaman and Reeder [5] ; Zaman [6] ; and Zaman, Reeder and Samimy [8] . One possible mechanism is the stripping and rolling up of the boundary layer by the tab.…”
Section: Modeling the Tabsmentioning
confidence: 99%
See 3 more Smart Citations
“…Possible physical mechanisms by which tabs produce streamwise vortices has been discussed by Samimy, Zaman and Reeder [5] ; Zaman [6] ; and Zaman, Reeder and Samimy [8] . One possible mechanism is the stripping and rolling up of the boundary layer by the tab.…”
Section: Modeling the Tabsmentioning
confidence: 99%
“…In the experiments of Samimy, e t a l . [ 5 ] and Zaman, et al [8] some of the con gurations were, in their words, \nominally laminar" and others \nominally turbulent". In both cases they found that the experimental results were virtually identical.…”
Section: Equationsmentioning
confidence: 99%
See 2 more Smart Citations
“…The first was the generation of streamwise vorticity in a similar manner to that of micro ramps 63 or tabs. 64 The second is the manipulation of the unsteadiness apparent in SBLI using the broad frequency range capability of LAFPA's. Dupont et al 65 showed that the upstream leg of a lambda shock wave oscillates at a Strouhal number of 0.03 while the downstream leg oscillates at a Strouhal number of 0.5.…”
Section: Applications Of Lafpa'smentioning
confidence: 99%